Why do large rivers tend to form multichannel? A field study in the Upper Paraná River - Stevaux, José C.; Gon, Priscila P. [UNESP]; Leli, Isabel T.; Fujita, Rafaela H. (Revista Brasileira de Geomorfologia, 2021)
Anastomosed rivers include a diverse group of fluvial forms with multiple and interconnected alluvial channels. They occur in a wide range of climates and reliefs and constitute the typical pattern of the mega rivers (Qm > 17,000 m3 s-1). Several authors have assumed that the development of an anabranching formation is the mechanism by which a channel maintains its maximum efficiency. However, this has only been tested by mathematical studies. In this study, we confirm this theory in a 58-km anabranching reach of the Upper Paraná River, through a hydraulic and bathymetric survey of 14 cross-sections. We conclude that where the slope can't increase, the channel reduces its w:d ratio, thereby maintaining its efficiency in the wider sections, according to the specific stream power equation (ω = ρgQs/w). The channel width and alluvial plain width are controlled by allochthonous factors (tectonic lineaments and bank composition). Although the nodal sections have the greatest efficiency, we confirmed that flow efficiency is maintained at a constant level of bedload transport and specific stream power along the anabranching reach.
Por que grandes rios tendem à canalização múltipla? Um estudo de campo no rio Paraná Superior
Keywords: Anabranching river; Large river; Maximum efficiency concept; Paraná River; Specific stream power